2012
DOI: 10.1128/jb.06306-11
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila LidA Affects Nucleotide Binding and Activity of the Host GTPase Rab1

Abstract: bLegionella pneumophila, the causative agent of a severe pneumonia known as Legionnaires' disease, intercepts material from host cell membrane transport pathways to create a specialized vacuolar compartment that supports bacterial replication. Delivery of bacterial effector proteins into the host cell requires the Dot/Icm type IV secretion system. Several effectors, including SidM, SidD, and LepB, were shown to target the early secretory pathway by manipulating the activity of the host GTPase Rab1. While the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…S7). We surmise that in the case of the WT, other host GTPases and their associated vesicles compensate for the lack of Rab1B recruitment, as previously postulated (112). Since the growth of the sidM mutant was also unaffected by depletion of Rab1B in U937 cells (Fig.…”
Section: Bmdm-ltmentioning
confidence: 81%
See 1 more Smart Citation
“…S7). We surmise that in the case of the WT, other host GTPases and their associated vesicles compensate for the lack of Rab1B recruitment, as previously postulated (112). Since the growth of the sidM mutant was also unaffected by depletion of Rab1B in U937 cells (Fig.…”
Section: Bmdm-ltmentioning
confidence: 81%
“…Since the growth of the sidM mutant was also unaffected by depletion of Rab1B in U937 cells (Fig. 7B), we inferred that the sidM mutant can still recruit other vesicles from the human host cell in order to support its growth (112). Most importantly, in contrast to the WT and the sidM mutant, the lspF mutant showed a 21% reduction in growth in Rab1B-depleted U937 cells compared to scramble U937 cells ( Fig.…”
Section: Bmdm-ltmentioning
confidence: 90%
“…Moreover, during infection, the spatio-temporal control of translocation and localization of SidM and AnkX might predominantly determine which modification occurs at a given time. Interestingly, LidA-bound Rab1 was found to be less prone to modification by both SidM and AnkX, suggesting that other effectors also indirectly impact on the intricate regulation of the modification status of Rab1 (Neunuebel et al 2012). …”
Section: The Deactivation and Release Of Rab1 From The Lcv Is Tightlymentioning
confidence: 99%
“…L. pneumophila also recruits the inositol polyphosphate-5-phosphatase OCRL1 to the LCV, which dephosphorylates PtdIns(4,5)P 2 , yielding PtdIns(4)P (18). The accumulation of PtdIns(4)P on the LCV serves as a membrane anchor for SidC and SidM (19,20), whereas LidA, SetA, and LpnE are localized to the LCV membrane and bind PtdIns(3)P in vitro (18,21,22), suggesting that the LCV membrane also contains PtdIns(3)P. The aim of the present study was to investigate the effector LtpD (23), which we found to bind both PtdIns(3)P and IMPA1.…”
mentioning
confidence: 99%